The Role and Status of English in Spanish-Speaking Argentina and Its Education System: Nationalism or Imperialism? - Porto, Melina (2014)
There is a lot of controversy nowadays in the field of English Language Teaching (ELT) in the context of Teaching English to Speakers of Other Languages (TESOL) regarding the status and role of English in non-English speaking countries, in particular in developing countries, as well as in English-speaking countries with a history of colonialism. In these settings, the discourse of English as a form of imperialism requires a reconsideration of the role and status of English in the national school curriculum in primary and secondary school contexts. It also requires the exploration of the connections with nationalism and national identity, for within this discourse of imperialism, English tends to be seen as detrimental to the national identity, which education explicitly aims to form and develop through formal schooling.